Letter to Editor: Do Iranian Medical Journal Editors Have a Good Knowledge, Attitude and Practice of Plagiarism? - Enjoo, Seyed Ali (Archives of Advances in Biosciences, 2018)
In the last issue of the Journal of Paramedical Sciences, Abbasiyan, et al in their Original Article “Do the editors-in-chief of Iranian medical journals have a good knowledge, attitude and practice of plagiarism” showed that the knowledge, attitude, and the practice (KAP) of the chief editors of scholarly journals in Iranian Medical Universities located in the capital city is in high and favorable level (1.58 out of 2) [1]. I would like to discuss the probable false messages of such articles for science ethical managers in the country. For some years, every several-months or several-years a scholarly paper or news has been published to show the ethics situation of academic researches or publication ethics in Iran periodically [2-5]. Some Iranian scientists think these reports are unfair [6], and some non-Iranian reporters named it a scandal [7] ; and yet, facts demonstrate little improvements with regards to ethical situation compared with the past. I believe that accepting the already existing problems is the first step for resolving them. Although I agree with Ataie-Ashtiani [8] and others who think that some magnifications have been made on the special case of IR Iran, as Farrokhi stated, unfortunately there are some problems including the presence of misconduct and also unawareness about how to explain and excuse when a mistake is discovered [9]. As I mentioned before, although there are some defects in our laws regarding managing academic dishonesty [10], there are also other regulations and newly approved rules [11] for such issues. Such hopeful studies [1] and laws [11] shows some attainments, while I still think it is essential to create a national organization to evaluate and disclose all cases of scientific misconduct and frauds and declare their punishments publicly. If such an organization to monitor and evaluate the integrity of researches exists, it should have clear equitable strategy to approach similar cases with different scientific degrees or other types of official power or position. As stated previously, although there are some defects in our laws to manage academic dishonesty [10], there are also other regulations and newly approved rules [11] to accomplish.